Message from Alfred Schnell to Max Bredig, May 23, 1942 - Schnell, Alfred (1942)
A message from Alfred Schnell (1900-1944) and Eva Schnell (1913-1944) to Max Albert Bredig (1902-1977). Alfred Schnell was a former colleague of Max Bredig. In the early 1940s, Alfred and his wife Eva fled to The Hauge to escape the persecution of the Jewish people in Germany. In 1943, German forces invaded the Netherlands and the Schnells went into hiding. In their messages to Max Bredig, they use aliases such as Arthur and Erna Dalem, Arthur and Ellen Escaper, and Alfred and Eva Kwik. In this letter, the Schnells tell Bredig that they are feeling hopeful and relaxed. While the message is dated May 23, 1942, it was not received until June 24, 1942.
Keywords: Bredig, Max Albert, 1902-1977; Schnell, Eva, 1913-1944; Schnell, Alfred, 1900-1944; Nederlandse Rode Kruis; World War (1939-1945); Jewish Holocaust (1939-1945)